Species-specific calcification response of Caribbean corals after 2-year transplantation to a low aragonite saturation submarine spring. Issue 1905 (26th June 2019) - Martinez, Ana; Crook, Elizabeth D.; Barshis, Daniel J.; Potts, Donald C.; Rebolledo-Vieyra, Mario; Hernandez, Laura; Paytan, Adina
Abstract : Coral calcification is expected to decline as atmospheric carbon dioxide concentration increases. We assessed the potential of Porites astreoides, Siderastrea siderea and Porites porites to survive and calcify under acidified conditions in a 2-year field transplant experiment around low pH, low aragonite saturation (Ωarag ) submarine springs. Slow-growing S. siderea had the highest post-transplantation survival and showed increases in concentrations of Symbiodiniaceae, chlorophyll a and protein at the low Ωarag site. Nubbins of P. astreoides had 20% lower survival and higher chlorophyll a concentration at the low Ωarag site. Only 33% of P. porites nubbins survived at low Ωarag and their linear extension and calcification rates were reduced. The density of skeletons deposited after transplantation at the low Ωarag spring was 15–30% lower for all species. These results suggest that corals with slow calcification rates and high Symbiodiniaceae, chlorophyll a and protein concentrations may be less susceptible to ocean acidification, albeit with reduced skeletal density. We postulate that corals in the springs are responding to greater energy demands for overcoming larger differences in carbonate chemistry between the calcifying medium and the external environment. The differential mortality, growth rates and physiological changes may impact future coral species assemblages and the reef framework robustness.